2013
DOI: 10.4314/tjpr.v12i5.11
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Cytotoxic Activities of Petroleum Ether Fruit Extract of Fruits of <i>Brucea javanica</i> (Simarubaceae)

Abstract: IC50 of 9.14, 12.45, 15.15, 16.13, 22.26, and 27.97 μg/mL against A549, CNE, HepG2,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
8
2
Order By: Relevance
“…Meanwhile, ethyl iso-allocholate was detected in PFME as well as F2, F3 and F5. The extracts of other plants that comprised ethyl iso-allocholate compound have also showed antiproliferative activities against MCF-7 and Hep G2 with IC 50 values within the range of 31.08 to 78.89µg/ml [34,46,47]. The current data contradicts to the mentioned studies as PFME showed no antiproliferative effects on MCF-7 and Hep G2 cancer cells.…”
Section: Antiproliferative Antioxidative and Compounds Identificatiocontrasting
confidence: 58%
“…Meanwhile, ethyl iso-allocholate was detected in PFME as well as F2, F3 and F5. The extracts of other plants that comprised ethyl iso-allocholate compound have also showed antiproliferative activities against MCF-7 and Hep G2 with IC 50 values within the range of 31.08 to 78.89µg/ml [34,46,47]. The current data contradicts to the mentioned studies as PFME showed no antiproliferative effects on MCF-7 and Hep G2 cancer cells.…”
Section: Antiproliferative Antioxidative and Compounds Identificatiocontrasting
confidence: 58%
“…The extracts of other plants that comprised ethyl iso-allocholate compound have also showed antiproliferative activities against MCF-7 and Hep G2 with IC 50 values within the range of 31.08 to 78.89µg/ml [34,46,47]. The current data contradicts to the mentioned studies as PFME showed no antiproliferative effects on MCF-7 and Hep G2 cancer cells.…”
Section: No Compoundscontrasting
confidence: 58%
“…The bacterial cells and fungal spore suspensions (10 6 CFU/ml) of each tested microbes were spread onto the nutrient agar plates for bacteria and potatoes dextrose agar plates for fungi. The wells (7 mm diameter) were dug on the inoculated plates [31], and 70 µl of purified pyocyanin (Needle-like crystals) dissolved in DMSO at different concentrations (3.75, 7.5, 15, 30, 60, 75, 100, 120 µg/ml) were added to the wells. The plates were left 2h at 4 o C to allow the diffusion.…”
Section: Protein Detection Of Phenazine Modified Gene (Phzs)mentioning
confidence: 99%